Illustrations Before Text Reduce Visuospatial Working Memory Load During Text Processing. Issue 8 (13th September 2020) - Schüler, Anne; Mayer, Maria Gabriela
ABSTRACT: In this study we investigated whether the beneficial effect of adding illustrations to text can be explained by the fact that illustrations facilitate analogous mental representation construction from text in visuospatial working memory. For this the secondary task paradigm was used. It was expected that the secondary task interfered only with learning from text when no illustrations were presented beforehand, because here learners have to construct an analogous mental model on their own, and consequently working memory load should be high. No interference of the secondary task was expected when illustrations were presented. Additionally, it was assumed that learners with illustration performed on a higher level. Contrast analyses confirmed this data pattern when reading (Experiments 1 and 3) or listening to the text (Experiment 2) and with less (Experiments 1 and 2) and more complex learning materials (Experiment 3) for recall tasks. These findings indicate that illustrations before text supported learners in constructing an analogous mental representation from the text, explaining why no secondary task interference was observed when illustrations were presented. The implications of these findings are discussed.